2010
DOI: 10.1093/jmedent/47.4.625
|View full text |Cite
|
Sign up to set email alerts
|

Detection of West Nile Virus RNA in Mosquitoes and Identification of Mosquito Blood Meals Collected at Alligator Farms in Louisiana

Abstract: Since 2001, alligator farms in the United States have sustained substantial economic losses because of West Nile virus (WNV) outbreaks in American alligators (Alligator mississippiensis). Once an initial infection is introduced into captive alligators, WNV can spread among animals by contaminative transmission. Some outbreaks have been linked to feeding on infected meat or the introduction of infected hatchlings, but the initial source of WNV infection has been uncertain in other outbreaks. We conducted a stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 25 publications
0
29
0
3
Order By: Relevance
“…nigripalpus were found to have fed on captive alligators in Louisiana. 45 A high rate of feeding on reptiles and amphibians was reported for Cx. quinquefasciatus in Puerto Rico during a period of elevated WNV transmission.…”
Section: Discussionmentioning
confidence: 98%
“…nigripalpus were found to have fed on captive alligators in Louisiana. 45 A high rate of feeding on reptiles and amphibians was reported for Cx. quinquefasciatus in Puerto Rico during a period of elevated WNV transmission.…”
Section: Discussionmentioning
confidence: 98%
“…columbiae is of interest, in light of research identifying WNV in nine pools of this species in New Mexico, 31 and in two pools captured at alligator farms in Louisiana. 32 Although this species seems to feed preferentially on livestock, 33 the degree to which it also feeds on small mammals, birds, or other vertebrates is not known. Our three positive pools came from a single outbreak site, a horse ranch, and those in New Mexico came primarily from semi-arid or agricultural sites.…”
Section: Discussionmentioning
confidence: 99%
“…Until its first detection in birds in Aus- viremic phase of infection in species such as humans or horses is in general too low to enable the infection of mosquitoes. However, it was shown by experimental infection that some mammalian species like fox squirrels (Sciurus niger) [129] or reptiles such as alligators [130] develop a viremia high enough to infect mosquitoes. In several European countries like France and Italy, WNV infections in horses were considered as the first signs of invasion of the pathogen into these regions [74,78].…”
Section: Usutu Virus (Usuv) Infectionsmentioning
confidence: 99%
“…This was demonstrated both by examining the progeny of experimentally infected mosquitoes as well as by virus isolation from male mosquitoes which must have been infected vertically because males do not take blood meals but rather feed on plant juice [130,150]. The transovarial transmission of the virus may be important for the maintenance of the infection cycle between mosquitoes and birds, as it has been shown that mosquitoes were infected with WNV during the winter diapause without having taken a blood meal [148].…”
Section: Evidence Of Wnv In European Mosquitoesmentioning
confidence: 99%